O golpe de 31 de Janeiro de 1891 : uma ousadia breve? - Cruz, Maria Antonieta (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This paper studies the republican rebellion of January 31st 1891, searching for both an explanation for the coupʼs failure and eventual effects it had on the republican movement in the period from 1891 to 1910. Attention is given to the circumstances surrounding the event, the reasons for choosing the city of Porto for its stage, the role of sergeants in the coup, the lack of support by the Partido Republicano Português (Portuguese Republican Party) and the repression of the coup. The paper also studies some of the reactions available in the newspapers of the period and some response texts published by institutions like the Porto City Hall (Câmara Municipal do Porto) or the Parliament - House of Commons (Câmara dos Deputados e Câmara dos Pares).